Prevalence and risk factors of Q fever (Coxiella burnetii) in cattle on farms of Limpopo province, South Africa - Sadiki, Vhahangwele; Gcebe, Nomakorinte; Mangena, Maruping L.; Ngoshe, Yusuf B.; Adesiyun, Abiodun A. (Frontiers in Veterinary Science, 2023)
Q fever in animals and humans and its economic and public health significance has been widely reported worldwide but in South Africa. There are few studies on the prevalence of this zoonosis and its associated risk factors in South African livestock. Therefore, a cross-sectional study was conducted to determine the seroprevalence, molecular prevalence, and risk factors associated with C. burnetii in cattle on farms in South Africa’s Limpopo province. Out of 383 cattle tested for antibodies, the overall seroprevalence was 24.28%. Herd size of >150 (OR: 9.88; 95%CI: 3.92–24.89; p < 0.01) remained associated with C. burnetii seropositivity in cattle. For PCR detection, targeting IS1111 fragment, cattle with no abortion history (OR: 0.37; 95%CI: 0.18–0.77; p < 0.01) and herd size of >150 (OR: 3.52; 95%CI: 1.34–9.24; p < 0.01) remained associated with C. burnetii positivity. The molecular prevalence in sheath scrapings and vaginal swabs by IS1111 PCR was 15.67%. Cohen’s kappa agreement test revealed a fair agreement between the PCR and ELISA results (k = 0.40). Sequence analysis revealed that the amplicons had similarities to the C. burnetii transposase gene fragment, confirming the presence of the pathogen. The higher seroprevalence than molecular prevalence indicated a past C. burnetii infection, no bacterial shedding through vaginal mucus in cows, or preputial discharge in bulls. Similarly, the detection of C. burnetii by PCR in the absence of antibodies could be partly explained by recent infections in which antibodies have not yet been produced against the bacteria, or the level of these antibodies was below the detectability threshold. The presence of the pathogen in cattle and the evidence of exposure, as shown by both PCR and ELISA suggests an active circulation of the pathogen. This study demonstrated that C. burnetii is widespread in the study area and that a herd size of >150 is associated with C. burnetii seroprevalence and molecular prevalence.